2020
DOI: 10.1002/ange.202004963
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Orthogonal Methyltransferases to Create Alternative Bioalkylation Pathways

Abstract: S‐adenosyl‐l‐methionine (SAM)‐dependent methyltransferases (MTs) catalyse the methylation of a vast array of small metabolites and biomacromolecules. Recently, rare carboxymethylation pathways have been discovered, including carboxymethyltransferase enzymes that utilise a carboxy‐SAM (cxSAM) cofactor generated from SAM by a cxSAM synthase (CmoA). We show how MT enzymes can utilise cxSAM to catalyse carboxymethylation of tetrahydroisoquinoline (THIQ) and catechol substrates. Site‐directed mutagenesis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…72, 79-81 For example, RnCOMT accepts carboxy-S-adenosyl-l-methionine (cxSAM) to enable carboxymethylation of 3,4-dihydroxybenzaldehyde with roughly 4:3 m-/p-selectivity. 82,83 The Y200L variant of this enzyme displayed improved m-/p-selectivity (64a' 64% and 65a' 3%), and similar selectivity trends were observed for 4-nitrocatechol. In a more recent study, an engineered halide methyltransferase (HMT) was evolved to accept ethyliodide as the alkyl donor to enable ethylation reactions.…”
Section: Alcohol Alkylationmentioning
confidence: 57%
“…72, 79-81 For example, RnCOMT accepts carboxy-S-adenosyl-l-methionine (cxSAM) to enable carboxymethylation of 3,4-dihydroxybenzaldehyde with roughly 4:3 m-/p-selectivity. 82,83 The Y200L variant of this enzyme displayed improved m-/p-selectivity (64a' 64% and 65a' 3%), and similar selectivity trends were observed for 4-nitrocatechol. In a more recent study, an engineered halide methyltransferase (HMT) was evolved to accept ethyliodide as the alkyl donor to enable ethylation reactions.…”
Section: Alcohol Alkylationmentioning
confidence: 57%
“…In addition to the possibility of broadening the diversity of radical SAM MT products by transferring alternative alkyl chains, this might be interesting in terms of using SAM analogues for mechanistic studies as has been shown before [36,37,84,85] . Together with the increasing number of available enzyme structures, it might be possible to design enzyme variants with a broader or altered substrate range, as has been shown for MATs and conventional MTs [88–91] …”
Section: Resultsmentioning
confidence: 99%
“…Enzymes are attractive alternatives for C-H functionalization because of their inherent chemoselectivity, sustainability, and potential to be optimized via protein engineering for tuning activity and stereoselectivity. [23][24][25][26][27][28] While natural enzymes capable of forging new carbon-carbon bonds via C(sp 3 )-H functionalization are rare and largely limited to specific substrates (e.g., methyl transfer reactions catalyzed by S-adenosylmethionine dependent enzymes) [29][30][31][32][33] , recent advances in protein engineering have expanded the repertoire of enzyme-catalyzed C-H functionalization via carbene transfer chemistry (Figure 2d-e). 23,34 Traditionally, C-H functionalization via metal-carbenoid insertion has been pursued through small molecule organometallic catalysts, including complexes with rhodium, [35][36][37] iridium, 38,39 and other metals.…”
Section: Introductionmentioning
confidence: 99%